Mонгол орны зарим алтны ордуудын хүдэржилт, гарал үүслийн харьцуулалт - C., Оюунгэрэл; Ч., Алтанзул; Л., Оюунжаргал; Б., Тамир; C., Минжинсор (Geological Issues, 2022)
The gold mineralization of Mongolia has been described by many geologists. Mongolian gold deposits and occurrences can be divided into 23 metallogenic belts. It shows that Mongolia has a very high potential in gold production. Epigenetic gold deposits and occurrences in Mongolia are genetically classified into several types: Au-Ag epithermal vein, orogenic, intrusion related, skarn, and porphyry, iron oxide-copper-gold deposit types. Mongolian orogenic deposits are structurally controlled and related to shear zones or folds, and are mostly hosted in granitoids or metasedimentary rocks, and metamorphic rocks. These Au deposits commonly occur as massive auriferous quartz veins that contain sulfides and less commonly occur as disseminated and stockwork. In this paper, the geological characteristics, sulfur isotopic geochemistry, and geochemical data of ore-forming fluids of five gold lode deposits in Mongolia such as Tavt deposit located in the Eg river-Dhzida metallogenic belt of the Eg-Dzhida metallogenic province, Gatsuurt, Harganat, Ereen, Biluut, Sujigtei, Ulaanbulag deposits of the Dzuunmod ore district located in the North Khentii metallogenic belt of the Khangai- Khentii metallogenic province, and Olon Ovoot group gold deposits located in the Ulziit metallogenic belt and Undurnaran deposit located n the Kharmagtai-Khunguut-Oyut Ulaan metallogenic belt of the South Mongolian metallogenic province, and Chandman Uul deposit in the of South Kherlen-Buyant metallogenic belt of the Central-Eastern Mongolia metallogenic province are comprehensively compared. The features of gold ore mineralization, fluid inclusion, and S isotope of gold deposits are summarized and analyzed.